Delayed type hypersensitivity-induced myeloid-derived suppressor cells regulate autoreactive T cells - Singh, Vibhuti; Mueller, Ulrike; Freyschmidt-Paul, Pia; Zöller, Margot (European journal of immunology, 2011)
Mild but efficient treatments of autoimmune diseases are urgently required. One such therapy, long-term maintenance of chronic delayed type hypersensitivity, has been described for alopecia areata (AA), a hair follicle-affecting autoimmune disease. The molecular mechanisms underlying the therapeutic efficacy are unknown, but may involve myeloid-derived suppressor cells (MDSCs). AA-affected mice were treated with squaric acid dibutyl ester (SADBE). The immunoreactivity of SADBE-treated AA lymphocytes and of AA lymphocytes co-cultured with SADBE-induced MDSCs was analyzed. The curative effect of SADBE was abolished by all-transretinoic acid, which drives MDSCs into differentiation, confirming a central role for MDSCs in therapeutic SADBE treatment. SADBE and SADBE-induced MDSCs strongly interfered with sustained autoreactive T-cell proliferation in response to AA skin lysate (autoantigen), which was accompanied by weak ζ-chain down-regulation and strongly impaired Lck activation. In contrast, activation of the mitochondrial apoptosis pathway and blockade of the anti-apoptotic PI3K/Akt pathway by SADBE-induced MDSCs did not require T-cell receptor engagement. Apoptosis induction correlated with high TNF-α expression in SADBE-induced MDSCs and elevated TNFRI levels in AA lymphocytes. SADBE-induced MDSCs interfere with persisting autoreactive T-cell proliferation and promote apoptosis of these T cells, which qualifies MDSCs induced and maintained by chronic delayed type hypersensitivity reactions as promising therapeutics in organ-related autoimmune diseases.
Gesehen am 14.10.2022